Financial Literacy Lifestyle Self Control and Student Consumptive Behavior: Literasi Keuangan, Gaya Hidup, Pengendalian Diri, dan Perilaku Konsumsi Mahasiswa - Iwan Kurniawan; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid growth of digital technology and e-commerce has transformed consumption patterns among young individuals. Specific Background University students, particularly active users of online marketplaces, are increasingly exposed to impulsive buying behavior driven by convenience and promotional features. Knowledge Gap Previous studies show inconsistent findings regarding the roles of financial literacy, lifestyle, and self-control in shaping consumptive behavior, and limited research integrates these variables within a single framework. Aims This study aims to examine the relationships between financial literacy, lifestyle, and self-control on student consumptive behavior. Results The findings reveal that financial literacy, lifestyle, and self-control each show a positive and significant relationship with consumptive behavior among students, supported by statistical testing using SmartPLS with 86 respondents. Novelty This study integrates three behavioral and financial variables within the context of student consumers using e-commerce platforms, offering a combined analytical perspective. Implications The results provide insights for improving financial awareness and behavioral control strategies among students to better manage consumption patterns in digital environments. Keywords: Financial Literacy, Lifestyle, Self Control, Consumptive Behavior, Students Key Findings Highlights Spending patterns linked with knowledge and financial decision skills Social and personal habits shape purchasing tendencies Internal regulation ability relates to buying decisions